2014
DOI: 10.1186/1471-2458-14-948
|View full text |Cite
|
Sign up to set email alerts
|

Association of dietary pattern and body weight with blood pressure in Jiangsu Province, China

Abstract: BackgroundTo identify risk factors, associations between dietary patterns, body mass index (BMI), and hypertension in a Chinese population.MethodsDietary intake was assessed in 2518 adults by a 3-day 24 h recall and a food frequency questionnaire. Salt and oil intake was assessed by weighing records. Four dietary patterns were identified using principal component analysis. Overweight and obesity was determined according to the Chinese cut-offs for BMI. High blood pressure was defined as systolic blood pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 40 publications
5
17
0
Order By: Relevance
“…Recently, several studies have indicated that there is a growing interest in medical research on the associations between overall dietary patterns and hypertension likelihood [15][16][17][18][19]. However, the findings from these studies remain inconsistent.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Recently, several studies have indicated that there is a growing interest in medical research on the associations between overall dietary patterns and hypertension likelihood [15][16][17][18][19]. However, the findings from these studies remain inconsistent.…”
Section: Introductionmentioning
confidence: 83%
“…Twenty-seven articles [9,13,[15][16][17][18][19][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] met the inclusion criteria and were included in this metaanalysis, including16 cohort studies [13,25,27,[30][31][32][34][35][36][37][38][39][40][41][42][43] and 11 cross-sectional studies [9, 15-19, 24, 26, 28-29, 33]. Descriptive information of each included study was presented in Table1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result may be not surprising, because Kolkata in Bengal has the “sweet culture,” the local daily sweet snacks or dessert consumption is rather high (Kar & Kundu, ). Conversely, the Chinese do not have dessert culture after main dishes and the sugar consumption on the daily eating table in Jiangsu is much less (Qin et al, ). Thereby, the local palate of people in West Bengal, India, due to higher exposition to sweetness may have been skewed to higher sweetness threshold level than that of people from east China.…”
Section: Discussionmentioning
confidence: 99%
“…Health Organization infant and young child feeding indicators, corresponded to the guidelines or healthy pattern by previous studies [11,16]. The traditional pattern was characterized by high intake of cereals, water and soup, other vegetables and fruits, meat, and multi-nutrient powders, similar to the traditional Chinese adults dietary patterns [17][18][19]. The breast milk pattern resembles the "breastfeeding" pattern reported by Lim [9] and Smithers [20], which was characterized by higher intake of breast milk and lower intake of formula milk.…”
Section: Discussionmentioning
confidence: 58%